Will the cows and chickens come home? Perspectives of Australian and Brazilian beef and poultry farmers towards diversification - Bogueva, Diana; Marques, M.; Molento, C.F.M.; Marinova, Dora; Phillips, Clive (MDPI AG, 2023)
Farmers across the world face criticism on environmental and animal welfare concerns, as well as are increasingly being affected by climate change. We explored the willingness of cattle and poultry producers in Australia and Brazil to consider alternative enterprises and diversification of their businesses. Twenty-seven farmers, 14 from Australia and 13 from Brazil, current or former beef or poultry producers, were interviewed to explore their perspectives about making such changes. The interviews were qualitatively analysed using Atlas.ti to generate key insights. Although the farmers were actively interested or had engaged in alternative enterprises, they recognised these presented a less certain future if they had been previously contracted to large companies. Some were critical of their respective governments and former contract companies for lack of assistance in finding suitable alternative enterprises. Farmers showed inconsistent recognition of the current challenges of animal production in relation to climate change. Our results indicate that most farmers are open to diversifying, but they face many challenges that have serious connotations. Public policies, knowledge transfer and a secure demand for alternative products emerged as major influential factors for Australian and Brazilian farmers in a fast and just transition from meat cattle and chicken raising to alternative activities.